Ingersoll Rand : a smarter, connected future - Williams, Jaime L., (SAGE Knowledge. Cases., 2018)
Ingersoll Rand (IR) recently reorganized to create new collaborations and spur growth to improve their business strategies and the company's bottom line. One main goal for IR was to take advantage of a boom in the emerging home automation industry. Looking at the projected growth of the industry, early entry into the market appears to be the most attractive way to diversify the firm. This case analyzes the home automation market and challenges to entry into such a market. The primary question is whether or not IR can change their business model from slow and methodical to a fast-paced innovation cycle necessary to secure early market entry to establish themselves in this new market.